The Bedford guide for college writers with reader, research manual, and handbook - Kennedy, X. J. (Bedford/St. Martins, 2007)
When it was first published twenty years ago, The Bedford Guide for College Writers brought a lively and innovative new approach to the teaching of writing. Since that time, authors X. J. and Dorothy M. Kennedy have won praise for their friendly tone and their view, apparent on every page of the text, that writing is the "usually surprising, often rewarding art of thinking while working with language." More recently, experienced teacher and writer Marcia F. Muth joined the author team, adding more practical advice to help all students — even those underprepared for college work — become successful academic writers.